The gamble between oncolytic virus therapy and IFN - Li, Qingbo; Tan, Fengxian; Wang, Yuanyuan; Liu, Xiaohui; Kong, Xianbin; Meng, Jingyan; Yang, Long; Cen, Shan (Frontiers in Immunology, 2022)
Various studies are being conducted on oncolytic virotherapy, and one of the mechanisms by which it exerts antitumor effects is mediating interferon (IFN) production. However, because IFN itself has an antiviral effect, this has a negative impact on oncolytic virus inhibition or tumor eradication. As a result, it is critical for the mechanism of IFN regulation by oncolytic viruses, and defining its mechanism of action is critical for improving the antitumor effect of oncolytic viruses. This review focuses on the regulatory mechanisms of IFNs by various oncolytic viruses and their combination therapies. At the same time, we briefly outline the pathways by which IFNs are produced and exerted, and we conclude by raising some current issues.